The mitochondrial genome of Coridius chinensis (Hemiptera: Dinidoridae) - Liu, Li; Li, Hu; Song, Fan; Song, Wen; Dai, Xun; Chang, Jian; Cai, Wanzhi (Zootaxa, 2012)
The nearly complete mitochondrial genome of Coridius chinensis (Dallas) is reported in this study. The mitogenome is a double-stranded circular molecule of more than 14,648 bp in length with an A+T content of 75.1%. It encoded 37 genes as in other insect mtDNAs, including 13 protein-coding genes (PCGs), 22 tRNA genes, 2 rRNA genes and a control region (unsuccessful sequencing), and the gene order is the same as most other known heteropteran mitogenomes. All of the 22 transfer RNAs can be folded into the typical cloverleaf structure except tRNASer(AGN), which can only form a simple loop at the site of dihydrouridine (DHU) arm as known in other metazoans. The secondary structures of the large and small ribosomal RNAs of C. chinensis are similar to other presented insects. The rrnL consisted of six structural domains and 40 helices, and the rrnS consisted of three structural domains and 26 helices. Nine PCGs are initiated with the standard initiation codons (ATN), while ND6 and ND1 use GTG, and COI and ATP8 use TTG. All PCGs stopped with TAA/TAG termination codons except the COII terminated with a single T residue. Asymmetry in the nucleotide composition between J-strand and N-strand was observed in this mitogenome.